Optimization of Process Flowsheets through Metaheuristic Techniques - Ponce-Ortega, José María; Hernández-Pérez, Luis Germán (Springer, 2019)
This book presents a general framework to implement a link between process simulators and optimization through metaheuristic techniques. The book describes step-by- step the methodology to implement this link for different process simulators and with different metaheuristic methods. The aim of this book is to provide the readers the needed knowledge to implement optimizations of process flowsheets through links between process simulators and metaheuristic approaches. This way, basic knowledge about simulation through process simulators is needed. To implement this link between process simulation and metaheuristic techniques, the approach is divided into three fundamental sections: process simulation, metaheuristic algorithm, and implementation of the link between process simulation and optimization, which are described in the following chapters. Chapter 1 presents some basic concepts needed. Chapter 2 presents an introduction about the general concepts that are involved in the process simulation and the main commercial software currently available to efficiently carry out this function. Chapter 2 also presents the basics about the management to manipulate simulations of chemical and industrial processes. Chapter 3 presents an introduction about metaheuristic optimization methods, which can be then included in the link to process simulators and optimization. Chapter 4 explains how to implement the link between the process simulators and optimization programs containing metaheuristic techniques, which correspond to the optimization of the flowsheet of the simulation of the process to be optimized. Chapter 4 also presents a detailed explanation of the presented methodology to implement the link between process simulators and optimization, which corresponds to the linking of programs. This part of the book is the main contribution of the proposed methodology. For its better understanding, the steps of the proposed methodology are first explained. Then, the needed code is provided to implement the appropriate link between simulation software and stochastic algorithms. For this purpose, the sequence to be followed is mentioned step by step, indicating how to call the needed variables.